2020
DOI: 10.3389/fchem.2020.00777
|View full text |Cite|
|
Sign up to set email alerts
|

Enhanced Electrochemical Properties of Catalyst by Phosphorous Addition for Direct Urea Fuel Cell

Abstract: An anode bimetallic catalyst comprising Ni-Pd alloy nanoparticles was loaded on acid-treated multi-walled carbon nanotubes (MWCNTs) for application in a direct urea fuel cell. The bimetallic catalyst and MWCNTs were synthesized by a hydrothermal method at 160 • C for 5 h. To reduce the catalyst particle size, alkaline resistance, and facilitate their uniform distribution on the surface of the MWCNTs, phosphorus (P) was added to the Ni-Pd/MWCNT catalyst. The effects of P on the distribution and reduction in siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Herein, the urea molecules with electron-donating amino groups and electron-withdrawing carbonyl groups can be selectively adsorbed on NNC via. Ni/ NiOO-carbonyl group as an intermediate step, 5,[26][27][28][29] followed by the corresponding nucleophilic OH − attack. As a result, cleavage of the C-N bond became more favourable, and UOR could proceed at a lower potential.…”
Section: Effect Of Koh Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Herein, the urea molecules with electron-donating amino groups and electron-withdrawing carbonyl groups can be selectively adsorbed on NNC via. Ni/ NiOO-carbonyl group as an intermediate step, 5,[26][27][28][29] followed by the corresponding nucleophilic OH − attack. As a result, cleavage of the C-N bond became more favourable, and UOR could proceed at a lower potential.…”
Section: Effect Of Koh Concentrationmentioning
confidence: 99%
“…To overcome this obstacle, finding alternative strategies to fabricate high-performance OER electrocatalysts is desirable. In recent years, it has been shown that anodic OER can be replaced with electrocatalytic oxidation of small molecules, such as urea, 4 benzyl alcohol, 5 and hydrazine, 6 which can considerably reduce the overpotential required for H 2 production.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the NiÀ Co catalyst was frequently adopted in literature, producing high power outputs ranging from 1.4 to 21.7 mW cm À 2 . [9,10,[20][21][22][23][24][25] Alternatively, NiÀ Cu, [26] NiÀ Pd, [27,28] NiÀ Cr, [29] and Ni-Fe [30][31][32] catalysts have also been explored. Among these Ni-based bimetallic catalysts, a layered double hydroxide (LDH) structure is especially advantageous owning to its unique properties such as tunable metal species and molar ratios.…”
Section: Introductionmentioning
confidence: 99%